Social innovation for health: engaging communities to address infectious diseases - Phyllis Dako-Gyeke; Uche V. Amazigo; Beatrice Halpaap; Lenore Manderson (BMC, 2020)
Abstract Universal health coverage emphasises the value of the community-based delivery of health services to ensure that underserved populations have access to care. In areas where infectious diseases are endemic, there are often few resources and limited capacity, and the introduction of effective and accessible strategies require innovation. In this special issue, the contributing authors emphasise the power of local responses to the circumstances that underpin diseases of poverty, and highlight the methodological and programme innovations necessary to support and sustain these responses. Through case studies, the authors illustrate how social innovations can address health inequities, and they identify the role of academics in the Social Innovation in Health Initiative to support this approach.